THE TYPES AND POWER RELATION OF DIRECTIVE SPEECH ACTS IN CLASSROOM INTERACTION - Septianingsih, Trias; Warsono, Warsono (English Education Journal, 2017)
Directive speech actsrefer to utterances produced bya speaker who wants the hearer to do something. This study aims to analyze the directive speech acts performed by lecturers and students, types of directive speech acts favoured by lecturers and students, the ways of directive speech acts related to the lecturer’s power. This study used directive speech acts theory proposed by Searle and Vanderveken (1985) and the theory of power proposed by Fairclough (1989) to analyze the data. The subjects of this study are collected from the lecturers and students of undergraduate program majoring in English Education. The result of this study showed that the lecturers used five types of directive speech acts in their classroom interactionsuch as requesting, suggesting, commanding, advising, and asking question. However, the students did not use directive speech act of advice. The most favoured directive speech acts used by the lesturers and the students was asking a question. The students asked questions when they did not understand the lesson or need answer to certain question. Directive speech acts were related to the lecturers’ power. It can be seen from the use of direct types of request, advice, and command.